Development of TPACK Based Interactive Media With a Problem Based Learning Model to Improve The 21st Century Skills of Elementary School Students in Pancasila Education Subjects - Triana, Nur Wira; Perangin-angin, Reh Bungana Beru; Ndona, Yakobus; Saragi, Daulat (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study investigates the feasibility, practicality, and effectiveness of TPACK-based interactive media with the Problem-Based Learning model to improve students' 21st-century skills in Pancasila Education. This research uses the Research and Development (R&D) method with the ADDIE (Analyze, Design, Develop, Implementation, and Evaluation) model. The subjects of this research consist of material experts, linguists, media experts, teachers, and 32 students of class V at SDIT Al-Farabi in North Sumatra. The data collection techniques used include observation, tests, and questionnaires. Data analysis techniques use qualitative and quantitative analysis. The results show that (1) the feasibility of the media was validated by subject matter experts with a percentage of 93.8% with very feasible criteria, linguists with 85.4% with very feasible criteria, and media experts with 90.3% with very feasible criteria, (2) practicality was yielded through a practicality test by teachers with a percentage of 100% with very practical criteria and student responses of 98% with very practical criteria, and (3) the effectiveness of students' 21st-century skills was obtained from students' critical thinking skills with an N-Gain (g) of 0.5 in the range of 0.3 ≤ g < 0.7 with the criterion of "Effective" and a Sig. of 0.000 < 0.05, which proved a significant improvement. Additionally, creative skills, communication, collaboration, and character of students showed a Sig. of 0.000 < 0.05, indicating a significant improvement, and students' citizenship skills showed a Sig. of 0.023 < 0.05, proving a significant improvement.